Some policy options for economic growth in South Africa - Aderibigbe, Olugbenga Olumuyiwa Adeniyi (University of Limpopo (Turfloop Campus), 2010)
Economic growth remains one of the key macroeconomic objectives of most governments. South Africa witnessed moderate economic growth rates between 1994 and 2006, except for 1998 when the country recorded a sharp decline in economic growth as a result of worldwide financial crisis. The key challenge facing the country is to sustain and improve on the growth performance. South Africa’s economic growth has largely been demand –driven as indicated by the dominance of consumption over investment. Growth theorists identify investment, savings, human capital, productivity and R & D as some of the principal drivers of economic growth on the supply side. Investment and savings within the economy remain largely below those of the world’s most successful East - Asian countries. Other indicators further reveal that there is still room for improvements on the supply-side of the economy. The growing current account deficits point to the fact that domestic demand is too high for the country’s productive capacity. Similarly, the declining enrolment in tertiary institutions and a shift in the structure of production towards high skill services industry call for a policy shift in line with the unfolding trend. Thus, this study proposes some policy options that could be considered to sustain South Africa’s economic growth performance. Key words: Economic Growth, Investments, Human Capital and Productivity
Thesis (M.Com. (Economics)) --University of Limpopo, 2010
Keywords: Policy; Economic growth; 338.9968; Economic development; Investments